2017
DOI: 10.9790/9622-0704010917
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Performance of 1MW Grid-connected PV system in Saudi Arabia

Abstract: In this paper, a feasibility study has been done utilizing real time solar irradiance data for a 1MW grid-connected PV system in Qassim region in the middle of Saudi Arabia. The analysis has been done using both technical and economic indicators. Technical performance indicators are; Yield Factor, Capacity Factor and Performance Ratio. Economic indicators are; Levelized cost of energy and simple payback time. The simulation results show high energy productivity, and both technical and economic indicators are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 8 publications
7
24
0
Order By: Relevance
“…Because of the various module efficiencies and array designs, the yield factor is used to measure the system's productivity. Yield factor is measured in kWh/kWp, by dividing the energy yield by the PV array's nominal power (P STC ) [27].…”
Section: Yield Factor (Yf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the various module efficiencies and array designs, the yield factor is used to measure the system's productivity. Yield factor is measured in kWh/kWp, by dividing the energy yield by the PV array's nominal power (P STC ) [27].…”
Section: Yield Factor (Yf)mentioning
confidence: 99%
“…This estimate was based on solar irradiance, while a stand-alone system with 85 MW capacity was analyzed. The study in [27] reported a total energy yield of 1 MW over the lifetime of a proposed 42,978.9 MWh grid-connected PV system in the Qassim region, assuming a 1% annual energy yield reduction due to project degradation. The yield factor, capacity factor, and performance ratio were analyzed as technical performance indicators, while the levelized cost of energy and payback period were used as economic performance indicators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis has been done using both technical and economic indicators such as Yield Factor, Capacity Factor and Performance Ratio, Levelized cost of energy and payback period. Almarshoud results [5] show high energy productivity, and both technical and economic indicators are high. A 10 MW photovoltaic grid-connected power plant commissioned at Ramagundam in India was studied whereas at this site average solar radiation about 27.3˚C [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had been made in the region to study the performance of such non-linear systems (solar electricity) so the economical outcome from such systems is compared and analyzed before engaging in further investment in such technology (solar PV installation). Almarshoud [5] studied the feasibility of utilizing real time solar irradiance data for a 1 MW grid-connected PV system in Qassim region in the middle of Saudi Arabia. An analysis has been done using both technical and economic indicators such as Yield Factor, Capacity Factor and Performance Ratio, Levelized cost of energy and payback period.…”
Section: Introductionmentioning
confidence: 99%